2017
DOI: 10.1109/twc.2017.2669963
|View full text |Cite
|
Sign up to set email alerts
|

Joint Device Positioning and Clock Synchronization in 5G Ultra-Dense Networks

Abstract: In this article, we address the prospects and key enabling technologies for highly efficient and accurate device positioning and tracking in fifth generation (5G) radio access networks. Building on the premises of ultra-dense networks (UDNs) as well as on the adoption of multicarrier waveforms and antenna arrays in the access nodes (ANs), we first formulate extended Kalman filter (EKF)-based solutions for computationally efficient joint estimation and tracking of the time of arrival (ToA) and direction of arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(163 citation statements)
references
References 50 publications
1
152
0
Order By: Relevance
“…), which is undesirable in a host of applications such as precise time and frequency transfer, or applications requiring highly accurate time synchronization of (data) signals. Further such applications are anticipated in the (near) future given for example the demanding timing requirements of autonomous manufacturing (e.g., synchronization of robots working together) and future 5G networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…), which is undesirable in a host of applications such as precise time and frequency transfer, or applications requiring highly accurate time synchronization of (data) signals. Further such applications are anticipated in the (near) future given for example the demanding timing requirements of autonomous manufacturing (e.g., synchronization of robots working together) and future 5G networks [3].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies have shown that errors on the order of a few centimeters can be achieved using a bandwidth of 100 MHz [2]. However, in order to achieve extreme ranging precision, other technological factors have to be considered, such as the imperfection of the internal clock-oscillator [3]. Not only the delay estimation accuracy increases with the bandwidth, but also the resolution improves.…”
Section: Cellular Positioningmentioning
confidence: 99%
“…In dense networks, devices can connect to a plurality of access nodes, which provides higher data rates with less energy consumption, under the condition that interference and mobility problems can be solved. If these challenges can be addressed and if access points can somehow announce their coordinates, ultra-dense networks can enable ultra-accurate positioning [3]. The reason is that positioning accuracy depends on not only the quality of the individual measurements (for which large bandwidths and many antennas are beneficial), but also the diversity and number of reference stations.…”
Section: Cellular Positioningmentioning
confidence: 99%
See 1 more Smart Citation
“…As it is shown in [20], Root Mean Square Errors (RMSEs) of coordinates' estimates is considerably dependent on the synchronism of the access nodes. The time servers places in the direct proximity of small cell would reduce time offsets, hence, improving the precision of positioning.…”
Section: Applicationsmentioning
confidence: 99%